Meniscal Injuries: Review - Khalid Muzzafar (Current Practice in Medical Science Vol. 9, 2022)
Meniscal injuries are common cause of pain and functional impairment in knee. Proper clinical examination and evaluation is must to diagnose the injury. Treatment in form of physical therapy can help sone patients, while surgical options like meniscal repair, partial menisectomy or total menisectomy is needed in some patients. Proper rehabilitation after surgery is required to get good functional results.